Accessible and Engaging Web Application for Increasing Customer Base and Purchasing Rate of Goods within the Retail Industry - H.S.T Weerasekara; I.N Magammulla; P.G.N Sashmitha; D.K Weerakkody; D.I.De Silva; R.R.P. De Zoysa (International Journal of Engineering and Management Research, 2022)
People generally prefer to shop online as it is more convenient and time-saving. Therefore, it makes sense for any type of business owner to use the internet to sell their goods. In order to increase the overall customer base as well as increase the purchasing rate of an average customer, there are many elements that need to be factored into an online clothing store application that will help improve customer satisfaction and aid in making the online store application successful. However, the process can be improved much further by implementing more advanced features which are not so common in competitive applications such as smart recommendations and providing more ways to visualize the items such as Augmented Reality and 3D models to visualize how the clothes would look on someone. The goal of this research is to discover how to incorporate such technologies and build a clothing store application that will improve the rate of customer purchasing and increase the overall customer satisfaction.